Análise funcional do design das órteses para rizartrose - Souza, Alessandra Cavalcanti de Albuquerque e (2006)
The purpose of this paper is to identify the utilization of two models of orthotics used in the conservative treatment of rizartrose in patients/consumers that were referred by the medical clinic to the LAI (Laboratory of Integrated Accessibility). It describes this group s perception related to the functional aspects of the two models, evaluates the value of the product attributed by the patient/consumer and describes the importance attributed to each model. The research s objective consists in identifying which model this is preferred from the point of view by the patients that use either the dorsal or ventral models used in the conservative treatment of rizartrose . This work is then based on the exploratory research through the investigation of the bibliography available and in the research field. The research field used the case study methodology to investigate the phenomenon in the real context. The data were collected using a patient questionnaire during two times after the use of the dorsal orthotic and after the use of the ventral orthotic. The questionnaire was used to identify the relationship between the patients/consumers and the two different types of orthotics. A general descriptive analysis was used in order to verify the patient s abilities executing certain activities daily living using the dorsal and ventral orthotics, the product s functional aspects and its value from the patient s/consumer s point of view. The results show that the preference for the dorsal or ventral models is determined by the individual needs of each person. The results also show that other variables, such as the use of the orthotic on the dominant or non-dominant hand, play a role in the preferred model by the patient/consumer and need to be further investigated